THE PANDIT: THE EMBODIMENT OF ORAL TRADITION - Cenkner, William (Journal of Dharma, 1980)
This study investigates the structure of oral tradition by defining the role of the transmitter in Hinduism, the pandit, Every scriptural tradition has its antecedent oral tradition, but some traditions place such great emphasis upon oral transmission that the scriptural canon itself takes oral form. For instance, the Druids of ancient Gaul never committed their wisdom to writing. The Celtic world, likewise, taught by a metrical and rhythmic oral transmission. Orthodox history, myth and ritual in classical Shinto were passed on orally by a hereditary priesthood of the Imperial Court. In fact, the prayers and rituals of Shinto were not set down jin writing until the 10th century A.D., even though the Japanese immediately placed Buddhist literature into written form.s In the history of Judaism there were two Torahs, one written and the other oral. The Hindu wisdom tradition has consistently valued oral transmission more than written transmission. Hindu scripture did not take written form for a millennium or longer after its canon was constituted.